[Muslims : ephemera material collected by the National Library of Australia]
The ephemera collection contains documents of everyday life generally covering publications of fewer than five pages. These may include: advertising material, area guides, booklets, brochures, samples of merchandise postcards, posters, programs, stickers and tickets.
Keywords: Muslims -- Australia -- Miscellanea; Islam -- Australia -- Miscellanea; Printed ephemera -- Australia; Australian